Susceptibility of Spodoptera frugiperda and Helicoverpa gelotopoeon (Lepidoptera: Noctuidae) to the entomopathogenic nematode Steinernema diaprepesi (Rhabditida: Steinernematidae) under laboratory conditions - Caccia, Milena Guadalupe (2014)
Spodoptera frugiperda Smith and Helicoverpa gelotopoeon (Dyar) are important agricultural pests ofseveral crops. The aim of the present work was to evaluate the susceptibility of larvae of both insects to an isolate of Steinernema diaprepesi Nguyen & Duncan under laboratory conditions, as well as the capacity of the nematode to multiply on the lepidoterans. Larvae (n = 15) were exposed to 0 (control), 50, and 100 infective juveniles (IJs) per Petri dish. Mortality was evaluated every 24 h during 6 d, and emerging IJs were counted. Mortality of S. frugiperda was 93% and 100% with 50 and 100 IJs dosage, and 87% and 93% in H. gelotopoeon, respectively. The production of IJs was significantly different between doses (P ≤ 0.05) for S. frugiperda (11 329 with 50 IJs vs. 27 155 with 100 IJs) but not for H. gelotopoeon 19 830 vs. 26 361, respectively). This is the first study evaluating the susceptibility of these lepidopterans to S. diaprepesi. These results encourage the possibility of using this nematode for biological control of both pests.